2021
DOI: 10.3390/nu13051391
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oro-Sensory Exposure on Satiation and Underlying Neurophysiological Mechanisms—What Do We Know So Far?

Abstract: The mouth is the first part of the gastrointestinal tract. During mastication sensory signals from the mouth, so-called oro-sensory exposure, elicit physiological signals that affect satiation and food intake. It has been established that a longer duration of oro-sensory exposure leads to earlier satiation. In addition, foods with more intense sweet or salty taste induce earlier satiation compared to foods that are equally palatable, but with lower taste intensity. Oro-sensory exposure to food affects satiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 112 publications
(155 reference statements)
1
20
0
1
Order By: Relevance
“…This agrees with a study in Europe that found that the diet characterized by irregular calorie consumption is associated with weight gain [15]. The current study results agree with the study by Lasschuijt and his colleagues have reported that overweight and obese men show an attenuated CCK response to unrestricted intake meals compared with normal-weight men [16]. Taste-signaling mechanisms specified in the oral cavity have an important role in detecting the taste; stimulation of taste receptors triggers regulatory circuits, which are essential in controlling eating behavior and regulating energy homeostasis [17].…”
Section: Discussionsupporting
confidence: 94%
“…This agrees with a study in Europe that found that the diet characterized by irregular calorie consumption is associated with weight gain [15]. The current study results agree with the study by Lasschuijt and his colleagues have reported that overweight and obese men show an attenuated CCK response to unrestricted intake meals compared with normal-weight men [16]. Taste-signaling mechanisms specified in the oral cavity have an important role in detecting the taste; stimulation of taste receptors triggers regulatory circuits, which are essential in controlling eating behavior and regulating energy homeostasis [17].…”
Section: Discussionsupporting
confidence: 94%
“…Harder foods have been shown to decrease eating rate and food intake by 9–21% across different foods and meals (see Table 1 in [ 20 •]). Both an increased number of chews and longer oro-sensory exposure have been suggested as reasons for the reduction of energy intake when eating harder foods at a slower rate [ 37 , 38 ]. However, it is important that the difference in perceived “hardness” should be sufficient to observe differences in eating rate and recent data demonstrates that adding fibers to brownies resulted in small changes to the structure that failed to impact oral processing behavior or eating rate.…”
Section: Food Texture Oral Processing Eating Rate and Energy Intakementioning
confidence: 99%
“…Satiation refers to the process that leads to the interruption of eating; therefore, it controls intake size, and is also known as "satiety during meals" 7 . Satiety is defined as the reduction in the desire to eat once the meal has finished; it refers to after-meal events that affect the interval until the next meal, thereby regulating meal frequency, and is also known as "satiety between meals" 8,9 . These processes are mediated by a series of physiological, cognitive and sensory mechanisms that together modulate the eating behavior 7 .…”
Section: Introductionmentioning
confidence: 99%